The The Importance of Screening Critical Congenital Heart Disease By Pulse Oximetry During Routine Neonatal Examination; Two Cases Reports: Neonatal examination and CCHD Screening - Hussain, Shabbir; Naseer, Nauman; Hussain, Moeez; Mehmood, Rana Usama Bin (Pakistan Armed Forces Medical Journal, 2022)
A male neonate was admitted for jaundice on the third day of life. On examination, baby was active, jaundiced, systemic examination revealed no abnormality except pulse oximetry difference of more than eight between pre and post ductal oxygen saturation. Later on, echocardiography revealed the diagnosis of hypo plastic left heart syndrome. The second case was a term female delivered by elective lower segment caesarean section. The first neonatal examination showed oxygen saturation of 70% with pre and post ductal difference of seven on routine pulse oximetry. Later on, pulmonary atresia, tricuspid atresia and patent duct us arteriosus were diagnosed on echocardiography. The patient was managed with prostaglandin to keep the duct open, followed by duct stenting.